2015
DOI: 10.1038/ejcn.2015.110
|View full text |Cite
|
Sign up to set email alerts
|

Association of diet and lifestyle with glycated haemoglobin in type 1 diabetes participants in the EURODIAB prospective complications study

Abstract: This study suggests that low intake of vegetable protein and dietary fibre are associated with worse glycaemic control in type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 53 publications
1
14
2
Order By: Relevance
“…The mean carbohydrate intake in the general population (221 ± 1 g/d in women; 276 ± 1 g/d in men) and in individuals with type 1 diabetes in a previous study (250.2 ± 81.6 g/d) is higher than in our study population [20,21]. A possible reason might be an underreporting of the carbohydrate intake, which has already been described as a major problem in the use of self-reported energy intake [22].…”
Section: Discussioncontrasting
confidence: 69%
“…The mean carbohydrate intake in the general population (221 ± 1 g/d in women; 276 ± 1 g/d in men) and in individuals with type 1 diabetes in a previous study (250.2 ± 81.6 g/d) is higher than in our study population [20,21]. A possible reason might be an underreporting of the carbohydrate intake, which has already been described as a major problem in the use of self-reported energy intake [22].…”
Section: Discussioncontrasting
confidence: 69%
“…In another study, no correlation between protein intake and time spent in hypoglycaemia, euglycaemia or hyperglycaemia was observed [11]. The longitudinal analyses of the EURO-DIAB study showed that, although baseline intakes of total protein did not determine glycaemia, intake of vegetable protein below the median (<29 g/day) was associated with worse glycaemic control [4]. In the prospective SEARCH Nutrition Ancillary Study, not only total protein intake but also vegetable and animal protein intakes predicted lower HbA 1c concentrations at the end of the mean 1.5 years of follow-up [19].…”
Section: Discussionmentioning
confidence: 96%
“…A 24‐week intervention with a high‐fibre diet (50 g/day), compared with a low‐fibre diet (15 g/day), significantly reduced mean daily blood glucose concentrations and the number of hypoglycaemic events . In the 7‐year prospective analyses of the EURODIAB study, baseline fibre intake below the median (<18 g/day) was associated with higher HbA 1c concentration . In addition to studies confirming the beneficial role of fibre, a number of studies were identified where no association between dietary fibre and glycaemia was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, about 422 million people worldwide have been diagnosed with diabetes that 10 percent of them with had Type I diabetes [5]. The disease affects one person from every 400 to 600 children [6] and 3-4 percent increases each year in European children [7].…”
Section: Editorialmentioning
confidence: 99%
“…In many countries, the amount of fiber intake in the diet of children and adolescents is lower than the recommended level [13]. Results of Balk et al study showed that low intake of vegetable protein and dietary fiber has been associated with poor blood glucose in control of Type I diabetes [7]. The fiber of processed foods is generally low; therefore, intake of fresh and unprocessed foods should be encouraged [13].…”
mentioning
confidence: 99%